Prospective randomised multi-centre trial comparing the clinical efficacy, safety and patient acceptability of circular stapled anopexy with closed diathermy haemorrhoidectomy. Issue 5 (17th December 2008) - Thaha, M A; Campbell, K L; Kazmi, S A; Irvine, L A; Khalil, A; Binnie, N R; Hendry, W S; Walker, A; Staines, H J; Steele, R J C
Abstract : Objective: Unlike excisional haemorrhoidectomy, stapled anopexy (SA), which does not involve radical excision, has theoretical advantages, thus offering potential patient benefits. We compared the clinical efficacy, safety and patient acceptability of SA, with closed haemorrhoidectomy (CH). Patients and methods: 182 patients with symptomatic haemorrhoids (grades II, III, IV) were randomly assigned to receive SA or CH and were followed for up to 1 year (6, 12, 24, 48 weeks) after operation. Postoperative pain, symptom control, complications, re-treatment rates, patient satisfaction, and quality of life were compared on an intention-to-treat basis. Results: Postoperative pain in the SA group (n = 91) was significantly lower (p = 0.004, Mann–Whitney U test). At 1 year there were no significant differences in the symptom load, symptom severity or the disease severity between the two groups. Overall complication rates were similar but faecal urgency was reported more frequently following SA (p = 0.093, Fisher's exact test). Despite a similar rate of residual symptoms, prolapse control was better with CH (p = 0.087, Fisher's exact test), and more patients in the SA group required re-treatment for residual prolapse at 1 year (p = 0.037, Fisher's exact test). However, more patients rated SA as an excellent operation at 6 and 12 weeks (p = 0.008 and 0.033, binary logistic regression) and were willing to undergo a repeat procedure if required (p = 0.018, Fisher's exact test). Conclusion: Stapled anopexy offers a significantly less painful alternative to excisional haemorrhoidectomy and achieves a higher patient acceptability. Although the overall symptom control and safety are similar in the majority of the patients, the re-treatment rate for recurrent prolapse at 1 year is higher following SA when compared to CH.